Methods for saving opioids in the perioperative period via intravenous, via neuraxial and in nervous blocks - Borja Mugabure Bujedo (Open Journal of Pain Medicine - Peertechz Publications, 2019)
The greatest challenge facing anesthesiologists in the current clinical context is to provide adequate perioperative care, achieving suffi cient control of acute pain and at the same time make responsible use of intraoperative opioids. There is a trending topic in our times that is based on saving perioperative opioids called Opioid free anesthesia (OFA) or to a lesser extent Opioid less anesthesia (OFA) to avoid the so-called opioid epidemic. All this is framed within appropriate protocols of care and post-operative recovery (ERAS).